Manajemen Prestasi Santri Berbasis Life Skills: Strategi Pembinaan Lanjutan di Pondok Pesantren Nurul Falah Al-Muttaqin - Zulfan Syahansyah (Tarbawi : Jurnal Studi Pendidikan Islami, 2024)
Purpose: While pesantren widely adopt life skills programs, how these skills translate into sustained achievement is underexplored. This study investigates: (1) How does a pesantren manage student achievements after life skills implementation? (2) How do students contribute to their own development? The objective is to analyze the synergy between institutional follow-up and student agency. Design/methodology/approach: A qualitative descriptive case study was conducted at Pondok Pesantren Nurul Falah Al-Muttaqin. Data were collected through interviews, observation, and documentation with alumni, then analyzed descriptively. Findings: The institution employs a structured follow-up system of mentoring and advanced specialization. Santri actively contribute by demonstrating agency, initiating projects, and forming peer groups. Findings indicate that achievement is co-created through the interplay of institutional support and student initiative. Research limitations/implications: As a single-case study, findings are context-specific. However, the results offer a practical model for other institutions to maximize the long-term impact of life skills education. Originality/value: This study moves beyond program implementation to the critical post-implementation phase. It uniquely illuminates the dynamic relationship between institutional strategy and student agency in fostering achievement, a perspective absent in prior literature.